Student Activism And The Repositioning Of The Girl Child In Zimbabwe's Tertiary Institutions. The Case Of Midlands State University Student Representative Council 2000- 2015 - Enock Nyajeka; Adele Mcilo; A. F. Chikerema (2023)
Student activism through SRCs has been there ever since inception of universities the world over. These were meant to represent the students at the decision making structures of the Universities. In Zimbabwe Gender mainstreaming has been advocated when admitting students in tertiary education and a quota system favoring the girl child has been advanced by the Ministry of Higher and Tertiary Education. Despite all these efforts by Government and universities to encourage and promote female student to participate in student politics, there has however been a lack of gender equality in terms of female student representatives. Female students who partake in the SRC have always been fewer than males and when they do they take up submissive posts with the highest being the Vice Presidency. A number of factors have been alleged to have been the cause of this phenomenon, that is, cultural, economic, political and social .Culturally,Ruminants of the patriarch society still exist and have stifled female participation in all sector of the economy and this has affected female students to partake in student politics. Norms and values of a patriarchal society still exist, where male domination values are upheld and the women’s space is confined to the private rather than the public sphere. The other internal factor that has harmed the female species from within is the known as the “Pull Her Down Syndrome” where females do little or nothing to empower each other but look down on each other and deliberately pull each other down publicly which maybe through hate speech.The participation of the female students is very minimal in student activism and decision making structures. However, an increase in enrolment has done very little in promoting the participation of the girl child in student activism. Thus, there is a need to promote their participation in student activism so they can be able to influence decisions and outcomes that affect their everyday lives in Tertiary institutions since they are the minority in terms of population size. Kurebwa (2013) also notes that the political presence of women is necessary for safeguarding that their interests, needs and concerns are incorporated in the policy process by their own input.